Evaluation Conformity Rejimen Peptic Ulcer Drug Therapy In Inpatient Care Facility At West Nusa Tenggara Regional Public Hospital - Recta Olivia Umboro; Fitri Apriliany; Vera Fitriya Ersalena (Parapemikir : Jurnal Ilmiah Farmasi, 2022)
Peptic ulcers are lesions in the stomach or duodenum caused by an imbalance between aggressive and mucosal protective factors. External factors such as smoking, coffee consumption, and helycobacter pylori infection are triggers for peptic ulcers. In 2017, there is an increase in the prevalence of gastritis (dyspepsia, peptic ulcer) in West Nusa Tenggara. The aim of this research to determine the description and appropriateness of drug therapy in patients with peptic ulcers. The observational method was used in this research with a descriptive cross-sectional study design. Data were collected retrospectively through tracing treatment  on the medical records of peptic ulcer patients at the in-patient facility of the West Nusa Tenggara Regional Public Hospital for the period January 2018 - January 2020. Based on inclusion and exclusion criteria, the number of prescriptions is 114 from 18 patients. The patient characteristic based on age was obtained between 55 – 64 years with a percentage of 50% with 55,56% suffered by men. The largest percentage of therapy was between PPI + Antacids + Sucraflat (38,89%). The percentage of the PPI group were omeprazole (88.89%) and lansoprazole (22.22%). In H2RA group, ranitidine (16.67%). Sucraflat (83.33%), ondansetron (33.33%) and antacids (55.56%). The percentage of the suitability of drug therapy is 88%. The percentage of dosage therapy appropriate is 100%.